A evasão escolar dos cursos técnicos integrados ao ensino médio do IFC Campus Concórdia: na perspectiva dos estudantes - Sbardelotto, Liane (2021)
School dropout has occupied space in discussions in various educational spheres of Professional and Technological Education. Although the context of the working world demands more and more qualification and improvement, it becomes a challenge for young people to stay and successfully continue the training process. This study aims to analyze the factors that contribute to school dropout from technical courses integrated to high school at IFC Campus Concórdia from the perspective of students; to analyze the Campus dropout rates in technical courses integrated to high school; and to outline the profile of young people who have dropped out of technical courses integrated to high school education on the Campus. Thus, the study proposes to discuss the factors of school dropout reported by students, taking into account their perceptions. For that, a theoretical review is carried out from the context of the creation of Professional and Technological Education (EPT) and the federal education system to understand education and work as a proposal to integrate high school and the challenges that are put to the contemporary young people in understanding the factors pointed out by the literature that leads them to abandon technical courses. This is qualitative research that consists of analysis of the document collection collected from RACI and SISAE and on the SIGAA and PNP platforms, composing information for the analysis of the evasion rates and dropout factors. The conduction of 12 individual semi-structured interviews with dropout students from the 1st, 2nd and 3rd years of technical courses integrated to high school in Agriculture, Food and Internet Information Technology, in the period 2017, 2018 and 2019, aimed to understand the dropout factors from the students’ perspective. The factors pointed out by the dropout students were categorized based on Bardin's (2016) content analysis. The results obtained in this research were based on the perception of evaded students and pointed to issues related to personal factors, which involve homesickness, difficulty in reconciling studies and work, in addition to the choice of the course, lack of identification in the course, misinformation related to the proposal of technical courses, as well as school factors related to the organizational dynamics of the courses, rigidity of the curricular components of general and technical training, high workload, content overload and evaluation processes. The research allowed us to conclude, within its limits, that, although the evasion factors pointed out by the participants are multifaceted and complex, the decision to evade is not the result of an impulse, but of an accumulation of mismatches and situations that reveal that the institution needs – on an ongoing basis – to think effectively about predictive strategies and actions to minimize dropouts and encourage young people to define and build their future projects.